From Tham Ting to Phu Phrabat: The overlay of beliefs and sacred areas of the people of the Mekong River Basin - Makmool, Prachatip (Asian Journal of Traditional and Innovative Arts and Textiles, 2024)
The article titled “From Tham Ting to Phu Phra Bat: overlay of beliefs and sacred spaces of the people of the Mekong River Basin” presents a study of the history of Tham Ting, Luang Prabang, Lao People’s Democratic Republic Including the history of Phu Phra Bat, Ban Phue District, Udon Thani Province, and the overlay of beliefs and sacred areas of Tham Ting and Phu Phra Bat. The results of the study found that Tham Ting and Phu Phra Bat are areas where beliefs and sacred areas of the Mekong River basin have overlapped since the prehistoric era, according to evidence found in antiques and paintings. Those who believe in the ghosts of their ancestors, spirits, sky ghosts, tan ghosts, fairies, and serpents were sacrificed before Brahmanism and Buddhism came to the area. When both religions entered the area. This caused the Dong Sai area to be transformed into a religious sacred place again. When King Fa Ngum of the Lan Xang Kingdom brought Buddhism to spread. Both places were transformed into Buddhist sites where Buddha statues, temples, stupas, relics, and various religious sites were built. That linked to folk legends and traditional beliefs. It has become a belief and a sacred space that is unique to the local area.